Controlling Greenhouse Gas Emissions Generated by the Transport Sector in ECA : Policy Options - Monsalve, Carolina (World Bank, Washington, DC, 2014)
Greenhouse gas emissions (GHG) generated from transport are among the fastest growing in Europe and in the Europe and Central Asia (ECA) region, posing a challenge in creating a low-carbon future, as economic development has been paralleled with a modal share increasingly dominated by roads.1 This modal shift, as in the European Union (EU), has been driven by a number of factors, including growing affluence, suburbanization, and falling land use densities in urban areas, which have translated into more widespread vehicle ownership, increasing trip numbers and lengths, while reducing the financial viability of public transport and non-motorized transport. This paper begins by reviewing recent trends in transport and GHG emission trends in the ECA region, using trends in the EU-15 and EU-27 as comparators.8 Subsequently, it will provide an overview of climate friendly transport policies for the road, rail, and air transport modes, before presenting some land transport success stories and then turning to a discussion on how to use revenues generated from pricing policy instruments. The objective is to provide a menu of policy options to improve the functioning of the transport sector in ECA, while addressing the externalities generated by the sector.